ANALISIS PENGARUH CLIENT SIZE, AUDIT FIRM SIZE, DAN AUDIT FEE TERHADAP AUDIT QUALITY - Muhammad Kafabih; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2017)
This research attempted to investigate the influences of client size, audit firm size, audit fee, toward audit quality. Client size, audit firm size, and audit fee expected to explain their influences toward audit quality.The data used by this research are secondary data taken from Indonesian Site Exchange (IDX) website that is manufactur companies listed from 2012-2015. This research uses purposive sampling method, and done data analysis that are descriptive analysis, classical assumption test, and regression test. This research used IBM SPSS 20 to analyzes the data.Based on the results, known that client size and audit fee have significantly positive influences toward audit quality. While audit firm size has significantly negative influence toward audit quality.